(3GjOGY GdChQGb GdeGdjI aj GdHfhc (B((3hOjYI GdUchc(B) :s (3OQGSI ebGQfI (B/s - (3GdHSWhjSj, GHQGgje GMeOs ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2009)
(3HjGf eGgjI hOjYI GdUchc,Jchjf YbO hOjYI GdUchc (B: (3GdMOjK Yf WQaj GdYbO , GdQVG aj GdYbO , eMd GdYbO , Qcf GdSHH aj GdYbO , BKGQ YbO hOjYI GdUchc h Pdc ef NdGd GdJRGeGJ GdehOY Edjg h GdehOY , EfgGA YbO hOjYI GdUchc dCSHGH fGTFI ef WHjYJg h dCSHGH fGTFI ef YhGed NGQLI Yfgs
(3eQGLY U(B.317s
Keywords: (3GdChQGb GdeGdjIs; (3GdHfhcs; (3GdTjcGJs; (3hOGFY GdHfcjIs